Electrochemical Characterization of a Cu(II)-Glutamate Alkaline Solution for Copper Electrodeposition - Pary, Paola (2015)
In this study, a cyanide-free electrolyte containing glutamate as a complexing agent is investigated as a more environmentally friendly alternative for alkaline copper plating. The solution was prepared using copper sulfate, sodium glutamate and potassium hydroxide. The pH of the electrolyte (pH = 8) and the ratio ligand:copper (R = 3), were chosen from equilibrium diagrams in order to avoid the formation of insoluble complexes and oxides. The electrochemical response of the system was determined by means of cyclic voltammetry. The results showed that copper electroreduction occurs in a two steps pathway with a cuprous-glutamate complex as an intermediate. Galvanostatic deposits obtained from the bath under study had proper brightness and roughness at the selected current density conditions. Scanning electron microscopy and X-Ray diffraction were carried out in order to characterize deposits surface morphology and crystal orientation. Chronoamperometric experiments together with atomic force microscopy proved that copper deposits grow through an instantaneous nucleation mechanism in which nuclei are not exactly spherical. These preliminary studies suggest that the Cu+2-glutamate electrolyte may be suitable for the replacement of cyanide baths in copper lectrodeposition at high pH without the need of additives as this electrolyte acts as a self-levelling system. Also, the use of this electrolyte could eliminate the need of performing strike deposits on less noble substrates, allowing a one step plating process.